2018
DOI: 10.1002/ejoc.201701538
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Ring‐Opening of Pyrazolo[3,4‐d][1,2,3]triazin‐4‐ones: An Experimental and Theoretical Study

Abstract: Several 3‐pyrazolylcarbonyl‐pyrazolo[3,4‐d][1,2,3]triazin‐4‐ones have been prepared from 5‐amino‐1H‐pyrazole‐4‐carbonitriles through a simple sequence. In the first step, diazotization of the corresponding aminopyrazoles afforded pyrazolo[3,4‐d][1,2,3]triazin‐4‐ones. Next, thermal rearrangement of these compounds through nitrogen elimination gave the final products. The proposed mechanism for the ring‐opening of the pyrazolotriazinones to give the pyrazolylcarbonyl‐pyrazolotriazinones involves the generation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This functional was extensively challenged by us and other authors to correctly describe complex heterocycles chemistries and yielded accurate mechanistic descriptions. For example, it has already been proved that this level of theory could give practically the same energy profiles than the much more computationally expensive MP4(DQ)/6‐311+G(d,p) for the syntheses of nitrogenated heterocycles as described recently . More specifically, for a gas‐phase process (no errors introduced by the solvent model, just the electronic structure description accuracy can be judged) the level of theory used here was very close to the CCSD(T)/6‐311+G(d,p), (maximum deviation in transition states relative energies below ca.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…This functional was extensively challenged by us and other authors to correctly describe complex heterocycles chemistries and yielded accurate mechanistic descriptions. For example, it has already been proved that this level of theory could give practically the same energy profiles than the much more computationally expensive MP4(DQ)/6‐311+G(d,p) for the syntheses of nitrogenated heterocycles as described recently . More specifically, for a gas‐phase process (no errors introduced by the solvent model, just the electronic structure description accuracy can be judged) the level of theory used here was very close to the CCSD(T)/6‐311+G(d,p), (maximum deviation in transition states relative energies below ca.…”
Section: Resultssupporting
confidence: 63%
“…Also for the sake of simplicity, the rapid release of water molecules will not be described (however, all intermediates and their energies are informed in the Supporting Information, SI, Table S1). This procedure has recently been fully justified in the study of a similar heterocycle synthesis, even though in that case the solvent was not as good proton donor as in this study …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…[ 11,12 ] Earlier studies reveal that there are numerous reported methods for elaboration of substituted pyrazolotriazine system relied on the diazotization of derivatives of 3‐aminopyrazole‐4‐carboxamide [ 13,14 ] and/or 3‐aminopyrazole‐4‐carbonitriles. [ 15,16 ] These aminopyrazoles were easily obtained either by the 1,3‐dipolar cycloaddition of nitrile imines, generated in situ from treatment of hydrazonoyl halides with a base, with active methylene nitriles [ 17 ] or from treating ketene‐N,S acetals with hydrazine hydrate. [ 12,18 ] Pyrazolotriazines are also considered as deazapurine analog, since the basic skeleton of purine and pyrazolotriazine is slightly similar.…”
Section: Introductionmentioning
confidence: 99%